Mycobacterial infections: features of microbiological diagnosis - A. V. Lutsenko; A. L. Yasenyavskaya; M. A. Samotrueva (Сибирский научный медицинский журнал, 2024)
To date, more than 200 species of mycobacteria have been identified, in addition to the well-known Mycobacterium leprae and Mycobacterium tuberculosis. Among microorganisms belonging to the genus Mycobacterium, there are obligate pathogenic, opportunistic and saprophytic strains. The incidence of non-tuberculous or atypical mycobacteria, which cause opportunistic infections in humans and animals, is steadily increasing. Non-tuberculous mycobacteria are increasingly recognized as a source of healthcare-associated infections.Aim of the study was to analyze the literature on current methods of microbiological diagnosis of mycobacterial infections.Material and methods. A search and analysis of scientific literature in the Web of Science, PubMed, eLIBRARY.RU, Europe PMC databases was performed using the following key words: mycobacteriosis, non-tuberculous mycobacteria, mycobacterial infections, MALDITOF MS, atypical mycobacteria. Results and discussion. The review summarizes and presents the classification, morphological, cultural, genetic and ecological features of mycobacterial strains. Modern approaches in the diagnosis of mycobacterial diseases and identification of pathogens are analyzed; their advantages and disadvantages are indicated.Conclusions. Mycobacterial infections are often considered as diseases associated with the provision of medical care, requiring a detailed assessment of the situation with the definition of criteria for microbiological monitoring of objects of a medical organization, etc. The analyzed literature data demonstrate a variety of methods for laboratory diagnosis of mycobacterial infections with the need for further improvement of methodological approaches.